Psychosocial work environment, organisational justice and work family conflict as predictors of Malaysian worker wellbeing - R Zirwatul Aida R Ibrahim (Melbourne, Australia: Victoria University, 2017)
This thesis investigates the predictors of Malaysian employee wellbeing, specifically, whether the psychosocial work environment (job demands, job control, social support), organisational justice (procedural, interactional, distributive) and work family conflict (work to family and family to work conflict) can reliably predict employee wellbeing (job satisfaction, job affective wellbeing, life satisfaction, positive affect, negative affect and psychological wellbeing).